2005
DOI: 10.1038/sj.leu.2403712
|View full text |Cite
|
Sign up to set email alerts
|

The t(8;17)(p11;q23) in the 8p11 myeloproliferative syndrome fuses MYO18A to FGFR1

Abstract: The 8p11 myeloproliferative syndrome (EMS) also known as stem cell leukemia-lymphoma syndrome (SCLL) is associated with translocations that disrupt FGFR1. The resultant fusion proteins are constitutively active tyrosine kinases, and different FGFR1 fusions are associated with subtly different disease phenotypes. We report here a patient with a t(8;17)(p11;q23) and an unusual myelodysplastic/myeloproliferative disease (MDS/MPD) characterized by thrombocytopenia due to markedly reduced size and numbers of megaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 23 publications
0
54
0
Order By: Relevance
“…26 MYO18B, encoded by a paralogue of MYO18A, is found at the centrosome. 21 Moreover, we have found that MYO18A interacts with CEP1 (L Daviet and D Birnbaum, unpublished).…”
Section: How Many Mpds Are Centrosomal Diseases?mentioning
confidence: 99%
“…26 MYO18B, encoded by a paralogue of MYO18A, is found at the centrosome. 21 Moreover, we have found that MYO18A interacts with CEP1 (L Daviet and D Birnbaum, unpublished).…”
Section: How Many Mpds Are Centrosomal Diseases?mentioning
confidence: 99%
“…[37][38][39][40] Additional fusion partners for FGFR1, including BCR, have since been described (Table 5). [41][42][43][44][45][46][47] The FGFR1 rearrangement can be found in both myeloid and lymphoid cells, suggesting an origin in a multipotent hematopoietic progenitor, and thus the basis for the disease's alternate designation of 'stem cell leukemia/ lymphoma syndrome.' EMS manifests an aggressive course and therefore early allogeneic transplantation is often recommended.…”
Section: Terminology and Classificationmentioning
confidence: 99%
“…3,6 Markedly, many of the translocation partner proteins identified to date are localized to the centrosome, a cell organelle, which contributes to cell-cycle control and organizes the mitotic spindle apparatus. [7][8][9][10][11][12][13][14][15][16][17][18] As the primary microtubule organizing center of most eukaryotic cells, the centrosome ensures symmetry and bipolarity of the cell division process, a function that is essential for accurate chromosome segregation. 19 Furthermore, cell-cycle progression into mitosis is initiated and controlled by cell-cycle regulatory proteins localized to the centrosome.…”
Section: Introductionmentioning
confidence: 99%